Electrocardiogram derived QRS duration associations with elevated central aortic systolic pressure (CASP) in a rural Australian population. Issue 1 (December 2015) - Lee, Yvonne; Reidler, Paul; Jelinek, Herbert; Lee, Yung; Zhou, Yuling; Hambly, Brett; McCabe, Joel; Matthews, Slade; Ke, Honghong; Assareh, Hassan; McLachlan, Craig
Abstract Background Prolonged electrocardiogram QRS durations are often present in hypertensive patients. Small increases in QRS duration serve as independent risk factors for both increased cardiovascular and all-cause mortality. Aortic stiffness is associated with increases in central aortic systolic blood pressure (CASP). However CASP and ECG QRS duration interactions have not been established in rural community populations. Our aims are to determine if QRS duration > 100 msec is associated with an elevated CASP measure in an Australian rural population. Methods A retrospective cross sectional population was obtained from the CSU Diabetes Screening Research Initiative data base where 68 participants had both central aortic pressure recorded and ECG derived QRS duration. Central aortic pressure was determined by directly recording radial arterial tonometry and brachial cuff pressure (HealthStats, Singapore). Resting 12-lead electrocardiograms were obtained from each subject using a Welch Allyn PC-Based ECG system. Results The population had a mean CASP of 137.8 mmHg, higher than previously reported in other population studies. In 8/68 subjects with a prolonged cardiac QRS duration >120 msec, CASP ranged from 129 mmHg – 182 mmHg. When subgroup analysis was stratified on the basis QRS duration <100 msec and ≥100 msec significant differences (p  = 0.036) were observed for mean CASP, 130.6 mmHg ± 15.6 (SD) versus 140.6 mmHg ± 16.8 (SD), respectively. Conclusions Our results suggest that an arbitrary CASP reading greater than a value 140 mmHg raises suspicion of a prolonged QRS duration. QRS durations ≥100 msec in an aging rural population are associated with higher CASP measures. Our results also suggest in aging Australian rural populations CASP is likely to be elevated, possibly due to age related aortic stiffening.